Corrosion Behavior of Fly Ash-Based Geopolymer Concrete - A. Wiratma; M.M. Al Bakri Abdullah; M.S.I. Ibrahim; T. Stachowiak; P. Vizureanu; F.F. Zainal; A. Romisuhani (Archives of Metallurgy and Materials)
This review paper investigates the corrosion characteristics of geopolymer concrete, which is considered a sustainable and environmentally friendly substitute for conventional concrete made with Portland cement. This study aims to consolidate the current understanding of corrosion mechanisms, the various factors contributing to corrosion, strategies for preventing corrosion, and the latest developments in this field. Geopolymer concrete has garnered considerable attention owing to its capacity to mitigate environmental impact and enhance the durability of concrete structures. A comprehensive understanding of a material’s vulnerability to corrosion is paramount to guaranteeing its sustained effectiveness over extended periods in diverse environmental conditions. Insights into the mechanisms of corrosion initiation and progression in geopolymer concrete have been derived from critical findings from experimental and theoretical studies. This paper examines the mechanisms of electrochemical corrosion, the characteristics of pore structure, permeability, and chemical composition, and the various factors that influence corrosion, such as environmental exposure and microstructural characteristics. This paper examines various methods for assessing corrosion, including electrochemical techniques, non-destructive testing, and microstructural analysis. Additionally, preventive measures such as material selection, coatings, sealants, cathodic protection, and inhibitors are discussed. Geopolymer concrete’s performance and challenges are exemplified through real-world case studies. The review provides a comprehensive summary of significant findings, implications, and areas for further research. It is a valuable resource fo